2015
DOI: 10.3389/fnins.2015.00044
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone mediates brain functional connectivity changes during the menstrual cycle—a pilot resting state MRI study

Abstract: The growing interest in intrinsic brain organization has sparked various innovative approaches to generating comprehensive connectivity-based maps of the human brain. Prior reports point to a sexual dimorphism of the structural and functional human connectome. However, it is uncertain whether subtle changes in sex hormones, as occur during the monthly menstrual cycle, substantially impact the functional architecture of the female brain. Here, we performed eigenvector centrality (EC) mapping in 32 longitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
83
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 83 publications
8
83
0
Order By: Relevance
“…Specifically, they observed a positive correlation between daily oestrogen level and microstructural integrity in the bilateral hippocampus with zero time lag, and the same oestrogen levels were negatively correlated with radial diffusivity. This paper extended previous papers that show menstrual cycle associated fluctuations in functional connectivity, particularly in the hippocampus (Ar elin et al, 2015;Lisofsky et al, 2015), by measuring on a daily basis. These in vivo findings from human neuroimaging studies further support the extensive evidence from animal research for an immediate subsequent effect of acute changes in oestrogen on brain plasticity across the menstrual cycle.…”
Section: Challenges In Researchsupporting
confidence: 69%
“…Specifically, they observed a positive correlation between daily oestrogen level and microstructural integrity in the bilateral hippocampus with zero time lag, and the same oestrogen levels were negatively correlated with radial diffusivity. This paper extended previous papers that show menstrual cycle associated fluctuations in functional connectivity, particularly in the hippocampus (Ar elin et al, 2015;Lisofsky et al, 2015), by measuring on a daily basis. These in vivo findings from human neuroimaging studies further support the extensive evidence from animal research for an immediate subsequent effect of acute changes in oestrogen on brain plasticity across the menstrual cycle.…”
Section: Challenges In Researchsupporting
confidence: 69%
“…Therefore, an investigation of the functional network properties of participants with diabetes and severe complications would be interesting. Third, numerous other factors of potential influence that deserve attention could not be investigated, for instance, the effects of sleep, fasting, estrogen/hormone medication, therapy compliance, and disease duration (45)(46)(47)(48). Finally, the effect of diabetes medication within the diabetes group (treated vs. untreated) should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding function, Lisofsky et al found that the connectivity between the HIPP and the superior parietal lobe was significantly strengthened during the late luteal phase. In addition, Arelin et al reported that the menstrual cycle substantially impacted intrinsic function and the connectivity of the HIPP with brain areas associated with contextual memory‐regulation . Taken together, these structural and functional imaging findings indicate that hippocampal changes are involved in menstrual cycle‐related variations.…”
mentioning
confidence: 91%
“…In addition, a functional connectivity (FC) method is used to describe the relationships between the neuronal activation patterns of anatomically distinct brain regions, revealing the level of functional communication between them . Two recent studies of resting state connectivity in females have demonstrated that the FC method shows sensitivity to investigate resting state connectivity data across the menstrual cycle . Thus, combining fALFF and FC may provide new insight into the complex role of the HIPP in the neural mechanisms of PMS.…”
mentioning
confidence: 99%